PENGELOLAAN KOMORBID PADA PANDEMI COVID 19 DI DESA SUMUR JOMBLANGBOGO KECAMATAN BOJONG KABUPATEN PEKALONGAN - Isrofah Isrofah; Ardiana Priharwanti; Irine Dwitasari Wulandari (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2022)
Background : People with comorbidities during the COVID-19 pandemic are one of the groups that are very vulnerable to being exposed to the virus. The number of people with hypertension is very large in Indonesia, hypertension is one of the groups that are vulnerable to being infected with COVID-19. Several studies have stated that groups of patients with hypertension and cardiovascular disease have a tendency to experience serious illness and death when infected with COVID-19. Therefore, in the hypertensive patient group, the correct management strategy is needed to avoid COVID-19 infection. Objective : This community service program aims to provide health education about comorbid management, manufacture of CERDIK Hypertension modules and ANKOR Gymnastics. The purpose of implementing this program is for the public to know how to manage hypertension correctly so that they can avoid the adverse effects of covid 19 on comorbidities. As a result of the program in the form of improving the quality of services to the public and scientific publications Method: This activity was attended by 20 participants who had previously taken the Covid-19 screening test to ensure this activity was safe to do at the Sumurjomblangbogo Village Hall. In addition, blood pressure measurements were carried out before and after the intervention. Pretest and Posttest were conducted to measure participants' knowledge before and after being given education. Result : this community service, can increase the knowledge of the respondents who were originally mostly knowledgeable (70%) to very good (90%). Similar activities are needed to develop youth posyandu cadres to have health maintenance skills. Of course, it takes support and participation from residents and village officials.